MANAJEMEN RESIKO PERBANKAN SYARIAH DI INDONESIA - Fasa, Muhammad Iqbal (Li Falah: Journal of Islamic Economics and Business, 2016)
Islamic banks will always be dealing with different types of risk with diverse complexity and inherent in its business activities. Thus, the implementation of risk management in Islamic banking is very urgent to be implemented in order to identify, measure, and control various risks to be faced. The discussion paper will discuss more in depth related risk management in Islamic banking in Indonesia theoretically and implementation. The discussion on worldview importance of risk management of Islamic banks, the identification of the risk characteristics of Islamic banks, the classification of the types of risks in Islamic banks, as well as the implementation of risk management deals in Islamic banks